Rook's textbook of dermatology - Burns, Tony , 1953-; Rook, Arthur (Wiley-Blackwell, 2010)
Covers different aspects of skin diseases from basic science through pathology and epidemiology to clinical practice. This title includes: coverage of cosmetic dermatology and sexually transmitted diseases; material on evidence-based dermatology; and, emphasis on therapeutics throughout the set.